Structure of P3HT in the solid state - Oliveira, Eliezer Fernando de [UNESP]; Lavarda, Francisco Carlos [UNESP] (Wiley-Blackwell, 2013)
Poly(3-hexylthiophene) (P3HT) is a polymer widely used in organic photovoltaic devices. Discrepancies in information exist in the literature about its morphological structure in solution and in the solid state. This work is a theoretical study, in which the structure of P3HT in the solid state is deduced from its structure in solution and comparisons with optical absorption data. The results indicate that P3HT is not planar, either in solution or in the solid state. However, the effective conjugation length in the solid state is similar to that of a planar chain. (c) 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2013, 51, 1350-1354
Keywords: computer modeling; conducting polymers; conjugated polymers; solid-state structure